2022
DOI: 10.3390/foods11070906
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroid Accelerates Wound Healing of Potato Tubers by Activation of Reactive Oxygen Metabolism and Phenylpropanoid Metabolism

Abstract: Wound healing could effectively reduce the decay rate of potato tubers after harvest, but it took a long time to form typical and complete healing structures. Brassinosteroid (BR), as a sterol hormone, is important for enhancing plant resistance to abiotic and biotic stresses. However, it has not been reported that if BR affects wound healing of potato tubers. In the present study, we observed that BR played a positive role in the accumulation of lignin and suberin polyphenolic (SPP) at the wounds, and effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…BRs are plant hormones that promote growth, improve plant stress resistance, and regulate the level of expression of chlorophyll synthase genes ( Ryo et al, 2022 ). BR can promote wound healing by activating reactive oxygen metabolism ( Han et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…BRs are plant hormones that promote growth, improve plant stress resistance, and regulate the level of expression of chlorophyll synthase genes ( Ryo et al, 2022 ). BR can promote wound healing by activating reactive oxygen metabolism ( Han et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…Lignin content was positively correlated with caffeic acid and coniferyl alcohol although the correlation was not significant. Previous studies [57][58][59] have demonstrated that the accumulation of lignin monomers is accompanied by an increase in the degree of lignification in plants. The signal of reactive oxygen species (ROS) generated by external environmental stress is also one of the reasons for plant lignification [60].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, a previous study reported that APX1 and SOD genes showed higher levels in SA- or CdCl 2 -treated potato plants, when compared to CK plants ( Li et al., 2019 ). Brassinosteroid (BR) activated the expression of the StPOD gene, and the expression level was partially increased in potato tubers at the end of wound healing ( Han et al., 2022 ). Some researchers believe that the highly active antioxidant enzymes are used to eliminate active oxygen, and the concentration of H 2 O 2 is reduced.…”
Section: Discussionmentioning
confidence: 99%